Copping out: Why police officers decline to participate in the sergeant’s promotional process - Whetstone, Thomas S. (American journal of criminal justice, 2001)
This work examines why police officers decline to participate in the first-line supervisor promotional process to the rank of sergeant. A mail survey, followed by focus group discussions, provides evidence that not seeking advancement is driven by considerations of family, lifestyle choices, and satisfaction with current assignment. Eligible officers who do not seek promotion may be more internally motivated and not driven by the extrinsic rewards attendant to upward mobility.